Respons Beberapa Kultivar Kacang Hijau (Vigna radiata L. Wilczek) terhadap Pemupukan Nitrogen Kedua Pada Awal Fase Reproduktif - Nusifera, Sosiawan; Simanjuntak, JS; Fitriani, MS (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2017)
Research aimed to know responses of several mungbean cultivars to second nitrogen fertilization at early reproductive stage and find the best dose for each cultivar, was conducted in experimental station of Faculty of Agriculture, Jambi University started from January 2016 until March 2016. This was a factorial experiment arranged in randomized block design with two replications. The first factor was mungbean cultivars comprised four levels namely ‘Betet’,’Walet’, ‘Parkit’, ‘Perkutut’ and the second factor was second nitrogen fertilization comprised three levels namely without second fertilization, 30 kg N ha-1 , 40 kg N ha-1 , 50 kg N ha-1 . Variables observed were period of reproductive stage (days), number of pod per plant, number of filled pod per plant, seed weight per plant (g), and 1000 seed weight (g). Data were analyzed by using analysis of variance continued with LSD test with significance level of 5%. Results indicated that there were different responses among four mungbean cultivars to second nitrogen fertilization at early reproductive stage, especially on variables of filled pod number per plant and seed weight per plant. Best dose for each cultivar was 40 kg N ha-1 for ‘Walet’ and 30 kg N ha-1 for Parkit, whereas on cultivar ‘Betet’ and ‘Perkutut’, second N fertilization seemed to have no significant effect.